2019
DOI: 10.1002/jmri.26548
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional connectivity of the marginal division in Parkinson's disease with mild cognitive impairment: A pilot resting‐state fMRI study

Abstract: Background The marginal division (MrD) is an important subcortical center involved in learning and memory. Mild cognitive impairment (MCI) is commonly seen in patients with Parkinson's disease (PD), but the neurobiological basis is yet to be elucidated. Purpose To use resting‐state functional magnetic resonance imaging (rs‐fMRI) to explore the altered functional connectivity (FC) of the MrD in patients with PD‐MCI. Study Type Prospective pilot study. Population Twenty‐five patients with PD‐MCI; 25 PD patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…Age . A total of 15 of 40 studies reported that patients with PD‐MCI were older than those without PD‐MCI (Supplementary Material 4), and our meta‐analysis confirmed that PD‐MCI patients were, on average, significantly older than patients without PD‐MCI with a significant and positive ES (= 0.36). The heterogeneity among the studies was moderate and significant.…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…Age . A total of 15 of 40 studies reported that patients with PD‐MCI were older than those without PD‐MCI (Supplementary Material 4), and our meta‐analysis confirmed that PD‐MCI patients were, on average, significantly older than patients without PD‐MCI with a significant and positive ES (= 0.36). The heterogeneity among the studies was moderate and significant.…”
Section: Resultssupporting
confidence: 69%
“…Of 21 studies, 8 revealed that PD‐MCI patients had higher H&Y stages than patients without PD‐MCI (Supplementary Material 5). Our meta‐analytic study showed that PD‐MCI patients had higher scores on the H&Y (Table ), with a significant and positive ES (= 0.33).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations